CYBERSPACE AND HUMAN RIGHTS - ÇOKBİLDİK, Anıl Cumali (Cyberpolitik Journal, 2017)
The most important parts of human rights legislation are the right to expression, opinion, personality and privacy in cyberspace. Freedom of statement, personal security and freedom, private life and the protection of personal data are often violated. These security issues, which emerged in parallel with the increasing technology in the field of communication and information technology, made it possible to take steps towards information law in the late stage. This study examines the historical development of human rights and cyber space, the dimensions of cyber space and human rights relation, human rights violations in cyberspace, and national, regional and international studies on the protection of these rights.